2012
DOI: 10.1242/jeb.067488
|View full text |Cite
|
Sign up to set email alerts
|

Proprioceptive feedback reinforces centrally generated stepping patterns in the cockroach

Abstract: SUMMARYThe relative importance of sensory input for the production of centrally generated motor patterns is crucial to our understanding of how animals coordinate their body segments to locomote. In legged locomotion, where terrain heterogeneity may require stride-by-stride changes in leg placement, evidence suggests that sensory information is essential for the timing of leg movement. In a previous study we showed that in cockroaches, renowned for rapid and stable running, a coordinated pattern can be elicite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 53 publications
3
36
0
Order By: Relevance
“…In addition, this observation posits a fine-grained behavioral manifestation of proprioceptive defects. A number of studies have shown that deciphering forces and proprioceptive feedback are important in generating stable patterns or gaits (Pearson, 1972;Ridgel et al, 2000;Zill et al, 2004;Fuchs et al, 2012) (for a review from a modeling perspective, see Holmes et al, 2006; for a review with a more biological perspective, see Delcomyn, 2004) and may 'directly influence [central pattern generators] and motoneurons to maintain phase relations in a decentralized, peripheral manner' (Holmes et al, 2006) through feedback. Proprioception has also been implicated in walking direction, for example, in stick insects (Akay et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, this observation posits a fine-grained behavioral manifestation of proprioceptive defects. A number of studies have shown that deciphering forces and proprioceptive feedback are important in generating stable patterns or gaits (Pearson, 1972;Ridgel et al, 2000;Zill et al, 2004;Fuchs et al, 2012) (for a review from a modeling perspective, see Holmes et al, 2006; for a review with a more biological perspective, see Delcomyn, 2004) and may 'directly influence [central pattern generators] and motoneurons to maintain phase relations in a decentralized, peripheral manner' (Holmes et al, 2006) through feedback. Proprioception has also been implicated in walking direction, for example, in stick insects (Akay et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Such signals not only contribute to coordination of the joints actuating each leg, but also help establish inter-leg coordination, as demonstrated by providing controlled sensory inputs to reduced, deafferented preparations during pharmacologically induced fictive walking-like motor patterns (e.g. [35]), or by manipulating specific sensory inputs in intact, walking preparations (e.g. [33,36 ]).…”
Section: The Cockroach Modelmentioning
confidence: 99%
“…Such reductions combine or blur biophysical details, but their efficacy can be tested. Specifically, phase-responsecurves, which quantify the receptivity of oscillators to inputs [16,35,51 ] and are used in computing coupling functions [30,55], can be estimated experimentally. Thus, phase reduced models can be compared directly with data.…”
Section: Toward Unified Modelsmentioning
confidence: 99%
“…Katz and Harris-Warrick, 1990), reinforcing rhythmicity (e.g. Fuchs et al, 2012) and, as discussed above for locusts, contributing to coordination of limb elements (e.g. Grillner and Zangger, 1979) or axial segments (Wen et al, 2012).…”
Section: Introductionmentioning
confidence: 83%